Evaluation of the Small Business Innovation Research Program in Japan. (February 2017) - Inoue, Hiroyasu; Yamaguchi, Eiichi
The Small Business Innovation Research (SBIR) program conducted by the Japanese government is intended to enable the rapid growth of small firms. Using comprehensive empirical data, this study examines the performances of firms that are directly affected by the program. First, to provide an outline, this study compares the changes in sales, employment, and the number of patents between SBIR awardees and matched firms. It cannot be shown that SBIR awardees have better performance using those indices. Second, this study conducts regression analyses to control for firm sizes, multiple awards, technological levels, the value of venture capital in a region, and population in regions. As a result, this study does not find that SBIR awardees have advantages after applying these detailed controls. This study shows that further detailed investigation is required to prove the benefit of the SBIR program.